JARINGAN SOSIAL PENDERES KARET DALAM PENJUALAN LEM KUKUT - Syahrani, Dinda; Gunawan, Gunawan (Universitas Tribhuwana Tungga Dewi, 2023)
The practice of selling lem kukut or rubber latex residue in the PTPN IX plantation of Kebon Ndowo Village takes place systematically so as to form a network within it. The wholesale rubber farmers sell the lem kukut they get from the company's plantations to middlemen. The buying and selling of lem kukut have been going on for a long time and are known by PTPN IX to be illegal. The purpose of this research is to analyze the social network that is formed in the selling system of lem kukut and the reasons for wholesale rubber farmers selling the remaining rubber latex to middlemen. The basis of this research uses Granovetter's attachment theory. This research was analyzed using qualitative methods. Data search techniques used are observation and in-depth interviews or deep interviews. The results showed that the social networks formed in the lem kukut sales system involved wholesale rubber farmers, PTPN IX, and middlemen. The reason for wholesale rubber farmers selling the remaining rubber latex or lem kukut to middlemen is that the weekly income they receive from PTPN IX is not enough to make ends meet.Praktik penjualan lem kukut atau sisa getah karet di perkebunan PTPN IX Desa Kebon Ndowo berlangsung secara sistematis sehingga membentuk sebuah jaringan di dalamnya. Penderes borongan menjual lem kukut yang didapatkan dari kebun perusahaan kepada tengkulak. Kegiatan jual beli lem kukut telah berlangsung lama dan diketahui oleh pihak PTPN IX sebagai tindakan ilegal. Tujuan penelitian ini adalah menganalisis jaringan sosial yang terbentuk dalam sistem penjualan lem kukut dan alasan penderes borongan menjual sisa getah karet kepada tengkulak. Landasan penelitian ini menggunakan teori keterlekatan Granovetter. Penelitian ini dianalisis menggunakan metode kualitatif. Teknik pencarian data yang digunakan adalah observasi dan wawancara mendalam atau deep interview. Hasil penelitian menunjukkan bahwa jaringan sosial yang terbentuk dalam sistem penjualan lem kukut melibatkan penderes borongan, PTPN IX, dan tengkulak. Alasan penderes borongan menjual sisa getah karet atau lem kukut pada tengkulak karena penghasilan mingguan yang mereka terima dari perusahaan PTPN IX tidak cukup untuk memenuhi kebutuhan hidup.